Analisis Perilaku Konsumen Terhadap Keputusan Pembelian Iphone Di Kalangan Mahasiswa - Namira Rahmi Rizqia; Nurhasanah; Syamsul Hidayat (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2024)
Communication is a social process in human life, one thing that is very basic and very necessary in human life. As time goes by, communication technology has become a basic need for various groups, initially telephones were only used to make calls and send messages, now they have developed into smart phones or smartphones which have many features so that smartphones have become an important need and a special priority among today's students. In this research study, many researchers have carried out consumer behavior, purchasing interest and purchasing decisions. Some related results from previous research are as follows: the first research was conducted by SH Amalia and SH Syahril (2017) with the title "Analysis of consumer behavior towards the iPhone purchasing decision process". This research aims to understand iPhone product management in depth about consumer behavior that will be the target, including the consumer decision making process. The method used in this research is quantitative or statistical. Quantitative research methods are methods used for research on certain populations or samples and are based on the philosophy of empiricism. Thus, this approach will allow analysts to find out the extent of consumer behavior towards iPhone users among Bina Bangsa University students in the city of Serang. It can be concluded that communication is a social process in human life, one thing that is very basic and very necessary in human life. As time goes by, communication technology has become a basic need for various groups of students. Initially telephones were only used to make calls and send messages, now they have developed into smart phones or smartphones which have many features so that smartphones have become an important need and a special priority among students today. This research was conducted to determine consumer behavior in iPhone purchasing decisions among students. Based on the introduction, theoretical studies and data processing as well as discussions that have been carried out in the previous chapter, the following conclusions can be drawn: consumer behavior variables have a significant influence on purchasing decisions.